2021
DOI: 10.3390/jpm11020100
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation in Allogeneic Hematopoietic Stem Cell Transplantation Recipients: A Systematic Review

Abstract: The disruption of gut microbiota eubiosis has been linked to major complications in allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. Various strategies have been developed to reduce dysbiosis and related complications. Fecal microbiota transplantation (FMT) consists of the infusion of fecal matter from a healthy donor to restore impaired intestinal homeostasis, and could be applied in the allo-HSCT setting. We conducted a systematic review of studies addressing the use of FMT in allo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Fecal microbiota transplantation (FMT) represents an alternative, more direct modulatory intervention using live microorganisms. The infusion of donor fecal matter is aimed at restoring GM eubiosis by replacing the bacterial communities harbored by the gut mucosa 72 . Bluestone et al reported the use of FMT to treat refractory Clostridioides difficile in 3 pediatric patients undergoing HSCT with no adverse effects, even if they achieved only one remission 73 .…”
Section: Gut Microbiome Modifications During Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) represents an alternative, more direct modulatory intervention using live microorganisms. The infusion of donor fecal matter is aimed at restoring GM eubiosis by replacing the bacterial communities harbored by the gut mucosa 72 . Bluestone et al reported the use of FMT to treat refractory Clostridioides difficile in 3 pediatric patients undergoing HSCT with no adverse effects, even if they achieved only one remission 73 .…”
Section: Gut Microbiome Modifications During Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Given the impact of intestinal microbiota diversity loss in the course of aGvHD, interventions to maintain intestinal diversity might contribute to improved outcomes. Numerous studies evaluated FMT as a treatment for steroid-resistant gut aGvHD, providing encouraging preliminary data regarding feasibility and efficacy that need to be confirmed in larger prospective studies [ 46 ]. van Lier et al reported that the response after FMT was accompanied by an increase in gut microbial α-diversity and an increased abundance of butyrate-producing bacteria, including the Clostridiales and Blautia species [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection control measures and regional epidemiology possess a significant role in the prevalence of CDI among individual medical centers, and our pooled estimation does not reduce the need for local centers to understand local prevalence. The meta-analysis showed that fecal microbiota transplantation, as an innovative strategy to reduce CDI occurrence, was recommended in patients with recurrent CDI in whom appropriate antibiotic treatments failed ( Pession et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%